"Canonical" Black Hole States in the Superluminal Source GRO J1655-40 - Méndez, Mariano R. (1998)
We analyze RXTE/PCA observations of the black hole candidate and galactic superluminal source GRO J1655-40 during its recent outburst. We show that during its decay to quiescence, GRO J1655-40 goes through the high, intermediate, and low state (and that at the beginning of its decay it might have even shown signatures of a very high state), just like other black hole candidates. This is the first time that such a transition is observed in a galactic superluminal source. We discuss what are the implications of these results on the hypothesis that the spin of the black hole in superluminal sources is much higher than in other black hole candidates.